Prevalence of ESBL-Producing Escherichia coli Isolated from elderly living at home setting in Mae Chai district, Phayao, Thailand - Supadej, Kanittapon; Nuanmuang, Narong; Baiubon, Pareeya; Kummasook, Aksarakorn (Naresuan University Journal: Science and Technology (NUJST); Vol 31 No 1 (2023): January - March 2023, 2022)
The prevalence of ESBL-producing bacteria has become a problem worldwide. This study aimed to investigate the existence of ESBL-producing E. coli isolates and their drug resistant genes that have become normal flora of the elderly population living in Phayao province. The fecal specimens from 252 elderly people were collected and drug resistant phenotypic screening was done by plating the samples on MacConkey agar supplemented with (1 µg/mL) cefotaxime or ceftazidime. The suspected E. coli isolates were identified with biochemical tests. Then, the phenotype of ESBL was confirmed by combination disk method and analyzed for bla TEM , bla SHV , and bla CTX-M-1 by PCR. In this study, 75 isolates (29.8%) were confirmed as suspected ESBL-producing E. coli . All confirmed isolates were multidrug resistant (MDR), and resistant to AMP, CTX, CRO, and CPD. However, all of them were susceptible to IMP, ETP, and MEM. There were 5 phenotypic β-lactam resistant patterns detected. The most predominant pattern was AMP CTX CAZ CRO FEP CPD ATM (55.4%). The genotypic characterization showed predominance of bla CTX-M-1 (35.7%) while there was no bla SHV detected. Moreover, the combination of bla TEM and bla CTX-M-1 together was detected at about 43%. This study showed there was high prevalence of ESBL-producing E. coli in elderly people residing in one regional community. These results suggest that ESBL may be transmitted via feces in communities of close-living quarters without good cleaning and hygiene practices. Keywords: ESBL-producing E. coli , elderly people, multidrug resistance, bla CTX-M , Thailand